Dietary Toll-Like Receptor Stimulants Promote Hepatic Inflammation and Impair Reverse Cholesterol Transport in Mice via Macrophage-Dependent Interleukin-1 Production - Faraj, Tola A.; Stover, Cordula; Erridge, Clett (Frontiers in Immunology, 2019)
Background: The mechanisms connecting dietary intake of processed foods with systemic inflammatory markers and cardiovascular risk remain poorly defined. We sought to compare the abundance of pro-inflammatory stimulants of innate immune receptors in processed foods with those produced by the murine ileal and caecal microbiota, and to explore the impact of their ingestion on systemic inflammation and lipid metabolism in vivo. Methods and results: Calibrated receptor-dependent reporter assays revealed that many processed foods, particularly those based on minced meats, contain pro-inflammatory stimulants of Toll-like receptor (TLR)-2 and TLR4 at concentrations which greatly exceed those produced by the endogenous murine ileal microbiota. Chronic dietary supplementation with these stimulants, at concentrations relevant to those measured in the Western diet, promoted hepatic inflammation and reduced several markers of reverse cholesterol transport (RCT) in mice. Hepatocytes were found to be insensitive to TLR2- and TLR4-stimulants directly, but their secretion of functional cholesterol acceptors was impaired by interleukin (IL)-1β released by TLR-responsive hepatic macrophages. Hepatic macrophage priming by high-fat diet enhanced the impairment of RCT by ingested endotoxin, and this was reversed by macrophage depletion via clodronate liposome treatment, or genetic deficiency in the IL-1 receptor. Conclusion: These findings reveal an unexpected mechanism connecting processed food consumption with cardiovascular risk factors, and introduce the food microbiota as a potential target for therapeutic regulation of lipid metabolism.